A method for efficiently separating different sized microplastic particles

CN117984469BActive Publication Date: 2026-10-16TONGJI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410269044.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-08
Publication Date
2026-10-16
Estimated Expiration
2044-03-08

AI Technical Summary

Technical Problem

[0006]该专利需要加入猪粪源溶解性有机质这一外源性物质二次负载针铁矿负载的多孔介质才能从混合液中分离出粒径较大的微塑料,过程较为复杂

Benefits of technology

[0027] 1. In this application, the preparation process of iron-loaded quartz sand is simple, low-cost, and the iron-loaded material is stable. When iron-loaded quartz sand particles were placed in a 0.01 mol/L NaCl background solution and shaken for 24 hours, no Fe precipitation was detected in the background solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117984469B_ABST
    Figure CN117984469B_ABST
Patent Text Reader

Abstract

The application discloses a method for effectively separating microplastic particles with different sizes. The method separates a mixed solution of two kinds of microplastics with different particle sizes through iron-loaded quartz sand. The prepared iron(hydro) oxide loaded quartz sand porous medium has increased surface roughness after iron loading, more abundant adsorption sites, and a Zeta potential changing from negative to positive, so that the microplastics can be combined through electrostatic attraction. Small-particle-size microplastics will compete with large-particle-size microplastics for limited adsorption sites on the surface of sand particles, and the combination ability of the microplastics with small particle sizes with the sites is stronger, so that the retention ability of the microplastics with large particle sizes in the porous medium is reduced, and the migration ability is increased. When the particle size ratio of the two kinds of microplastics is lower than 1:5, the separation effect is remarkable. The iron(hydro) oxide preparation and loading method is simple, and the separation process is simple and feasible. The microplastics with different particle sizes can be effectively separated, and the method has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for separating microplastics, and more particularly to a method for effectively separating microplastic particles of different sizes. Background Technology

[0002] Microplastics are plastic particles with a diameter of less than 5 mm. They cause widespread pollution, reaching every corner of the globe. Microplastics can act as carriers of pollutants, transporting them and posing potential environmental risks.

[0003] Filter media such as quartz sand often carry a negative charge on their surface, and microplastics of various particle sizes also carry a negative charge on their surface. The interaction between microplastic particles and sand particles is mainly a weak electrostatic repulsion. Therefore, traditional sand filtration methods cannot achieve selective separation of microplastics of different particle sizes.

[0004] Iron (hydride) oxides are often used to modify porous media such as quartz sand, and their presence affects the migration of microplastics in porous media. Studies have shown that iron (hydride) oxide particles promote the aggregation of microplastic particles on the surface of porous media (Cotransport and Deposition of Iron Oxides with Different-Sized PlasticParticles in Saturated Quartz Sand[J].Environmental Science & Technology, 2019, 53(7): 3547-3557.), thereby increasing the retention of microplastics in the sand column. After iron loading, the surface potential of the sand particles changes from negative to positive, and the surface roughness of the sand particles increases significantly, resulting in more adsorption sites. Therefore, the carrier sand particles can retain more negatively charged microplastics.

[0005] Chinese patent CN114619588A discloses a method for separating microplastics and nanoplastics in a porous medium using soluble organic matter extracted from pig manure and goethite. The method includes the following steps: 1) preparing goethite; 2) preparing a porous medium loaded with goethite by mixing goethite with quartz sand and filling the mixture in layers into a glass chromatography column; 3) extracting and purifying the soluble organic matter from pig manure; 4) recovering the nanoplastics and microplastics by passing 200 mg / L 50 nm nanoplastics and 50 mg / L 400 nm microplastics into the porous medium loaded with goethite, which separates the nanoplastics from the mixture; and by passing 200 mg / L 50 nm nanoplastics and 50 mg / L 400 nm microplastics into a porous medium loaded with goethite secondary-loaded soluble organic matter from pig manure, which separates the microplastics from the mixture.

[0006] This patent requires the addition of exogenous substances such as soluble organic matter from pig manure to a secondary loading of a porous medium loaded with goethite in order to separate microplastics with larger particle sizes from the mixture, which is a relatively complex process. Summary of the Invention

[0007] Objective of the Invention: The objective of this invention is to provide an effective method for separating microplastic particles of different sizes. This method utilizes the strong retention capacity of iron-loaded sand particles for small-diameter microplastics and the competitive adhesion of these small-diameter microplastics to achieve selective separation of large-diameter microplastics in a mixed solution. The separation mechanism of the two microplastic sizes is the competitive adhesion of microplastic particles of different sizes to the surface of iron-loaded sand particles. During co-migration, the lower energy barrier between small-diameter microplastic particles makes them more likely to aggregate on the surface of iron-loaded sand particles, preferentially occupying attachment sites on the sand particle surface and repelling the retention of large-diameter microplastics within the sand column. Accordingly, large-diameter microplastic particles can be separated from a mixed solution of microplastics of two sizes.

[0008] The prepared iron (hydrogen) oxide-supported porous quartz sand medium exhibits increased surface roughness and more abundant adsorption sites after iron loading, resulting in a change in the zeta potential from negative to positive. This allows for the binding of microplastics through electrostatic attraction. Small-diameter microplastics compete with larger-diameter microplastics for the limited adsorption sites on the sand grain surface. However, the smaller-diameter microplastics exhibit stronger binding ability to these sites, leading to a decrease in the retention capacity of larger-diameter microplastics within the porous medium and an increase in their migration capacity, thus achieving separation.

[0009] Technical solution: The method for effectively separating microplastic particles of different sizes described in this invention involves passing a mixed solution of two microplastics with different particle sizes into an iron-loaded quartz sand column, where they are separated through competitive adhesion.

[0010] Furthermore, the preparation method of the iron-loaded quartz sand is as follows: quartz sand is placed in Fe(NO3)3 aqueous solution and mixed thoroughly, the pH is adjusted to alkaline, and the mixture is shaken and mixed. Then the pH is adjusted to acidic, and the mixture is shaken again. Finally, the iron-loaded quartz sand is washed until it no longer discolors.

[0011] Further, the pH of the solution was adjusted to 10 using NaOH.

[0012] Further, the pH of the mixture was adjusted to 6 using HCl.

[0013] Furthermore, the prepared iron-loaded sand particles were packed into a glass chromatography column for the separation of mixed solutions of microplastics with different particle sizes.

[0014] Furthermore, the sample is injected from the lower end of the sand column, and the upper end of the flexible tube is connected to the recovery tube and the sampler, with the injection flow rate controlled at 1.5-2.5 mL / min.

[0015] Furthermore, the microplastic mixture is passed through a 40-60 mesh sand column.

[0016] Furthermore, the concentration of both types of microplastics in the mixed solution was 10 mg / L, and a microplastic mixed solution with a pore volume of 38 was continuously introduced.

[0017] Furthermore, the iron loading of the iron-loaded quartz sand particles is between 300-700 mg / kg, preferably between 419.40-663.06 mg / kg.

[0018] Furthermore, the particle size range of the microplastics is 10-1000 nm, preferably 100-800 nm; and / or, the particle size ratio of small-diameter microplastics to large-diameter microplastics is less than 1:5; and / or, the background solution for preparing the mixed solution of microplastics is a NaCl solution, preferably a 0.01 mol / L NaCl solution.

[0019] The preferred method for effectively separating microplastics of different sizes comprises the following steps:

[0020] (1) Preparation of iron-loaded quartz sand

[0021] Mix 40-60 mesh quartz sand thoroughly in a 0.04 mol / L Fe(NO3)3·9H2O solution. Add NaOH solution to adjust the pH to 10. Shake the mixture on a shaker for half an hour. Then, adjust the pH of the mixture to about 6 with HCl (volume fraction 2:3). Shake the mixture on a shaker for 24 hours. Wash the iron-loaded quartz sand with deionized water until it no longer discolors. Dry it in a 60℃ oven.

[0022] (2) Filling of the iron-loaded sand column

[0023] The iron-loaded sand particles were thoroughly wetted with a 0.01 mol / L NaCl background solution and then packed into a glass chromatography column with an inner diameter of 1.0 cm and a height of 10 cm. 300-mesh filters were fixed at both ends of the column to prevent quartz sand loss. Before packing, a certain level of 0.01 mol / L NaCl background solution was pumped into the column using a peristaltic pump. During packing, the liquid level in the column was ensured to always be slightly higher than the quartz sand. After each batch of sand particles was packed, the column was gently tapped with a rubber mallet to avoid introducing air bubbles. The porosity of the iron-loaded sand particles in the column was 45.8%.

[0024] (3) Separation of microplastics

[0025] The sand column was sampled from the bottom, with the top injection tube connected to the recovery tube and sampler. A peristaltic pump controlled the injection. Before sampling, the column system was equilibrated with 0.01 mol / L NaCl solution for 30 minutes to ensure stability. Two microplastic solutions with different particle sizes (10 mg / L concentration, background ionic strength 0.01 mol / L NaCl) were passed into the sand column, totaling 38 pore volumes. The eluent was collected using a sampler. Only large-diameter microplastics could penetrate the sand column; small-diameter microplastics were almost completely retained within it.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] 1. In this application, the preparation process of iron-loaded quartz sand is simple, low-cost, and the iron-loaded material is stable. When iron-loaded quartz sand particles were placed in a 0.01 mol / L NaCl background solution and shaken for 24 hours, no Fe precipitation was detected in the background solution.

[0028] 2. In this application, the microplastic separation process is simple and feasible, and no exogenous substances need to be added. The particle size range of the microplastics is 10-1000nm. The particle size ratio of the two microplastics only needs to be less than 1:5 to obtain a good separation effect.

[0029] 3. Compared with existing separation methods, the material preparation method of this invention is simpler and the microplastic separation process is more convenient and feasible, showing good application prospects. Attached Figure Description

[0030] Figure 1 A simplified diagram of the separation method;

[0031] Figure 2 The graph shows the changes in the penetration concentration of 200 nm and 1000 nm microplastics in an iron-loaded sand column;

[0032] Figure 3 SEM image of the surface of the iron-loaded sand particles;

[0033] Figure 4 The calculated DLVO energy between 200nm and 1000nm microplastic particles;

[0034] Figure 5 The graph shows the changes in the penetration concentration of 100 nm and 800 nm microplastics in an iron-loaded sand column (flow rate 1.5 mL / min).

[0035] Figure 6 The graph shows the changes in the penetration concentration of 100 nm and 800 nm microplastics in an iron-loaded sand column (flow rate 2.0 mL / min). Detailed Implementation

[0036] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.

[0037] Example 1:

[0038] (1) Preparation of iron-loaded quartz sand

[0039] Mix 40-60 mesh quartz sand thoroughly in a 0.04 mol / L Fe(NO3)3·9H2O solution. Add NaOH solution to adjust the pH to 10. Shake the mixture on a shaker for half an hour. Then, adjust the pH of the mixture to about 6 with HCl (volume fraction 2:3). Shake the mixture on a shaker for 24 hours. Wash the iron-loaded quartz sand with deionized water until it no longer discolors. Dry it in a 60℃ oven.

[0040] (2) Filling of the iron-loaded sand column

[0041] The iron-loaded sand particles were thoroughly wetted with a 0.01 mol / L NaCl background solution and then packed into a glass chromatography column with an inner diameter of 1.0 cm and a height of 10 cm. 300-mesh filters were fixed at both ends of the column to prevent quartz sand loss. Before packing, a certain level of 0.01 mol / L NaCl background solution was pumped into the column using a peristaltic pump. During packing, the liquid level in the column was ensured to always be slightly higher than the quartz sand. After each batch of sand particles was packed, the column was gently tapped with a rubber mallet to avoid introducing air bubbles. The porosity of the iron-loaded sand particles in the column was 45.8%.

[0042] (3) Separation of 200nm and 1000nm microplastics (particle size ratio 1:5)

[0043] The sand column was sampled from the bottom, with the top injection tube connected to the recovery tube and sampler. A peristaltic pump controlled the injection. A mixed solution of 200 nm and 1000 nm microplastics was prepared using 0.01 mol / L NaCl solution as the background solution. The concentration of both microplastics in the mixed solution was 10 mg / L. The iron loading of the sand particles was 663.06 mg / kg. After packing the sand column, the 0.01 mol / L NaCl background solution was pumped into the sand column at a flow rate of 1.5 mL / min for 30 minutes using a peristaltic pump to equilibrate the column system and ensure its stability. Then, a mixed solution of microplastics with a pore volume of 38 was continuously pumped in. The effluent was collected every 6 minutes using a sampler, and the concentration of microplastics in the effluent was measured. The concentrations of the two microplastics in the effluent were determined using a dual-wavelength ultraviolet method, and a concentration change graph was plotted. Figure 2 As shown.

[0044] from Figure 2 It can be seen that as the injection time changes, the 200nm microplastics are almost completely retained inside the sand column, while the 1000nm microplastics will pass through the sand column, thus achieving the separation of 1000nm microplastics in the mixed solution.

[0045] Table 1 shows the surface zeta potentials of the microplastics and sand particles before and after iron loading. After iron loading, the surface potential of the quartz sand particles changes from negative to positive, indicating an electrostatic attraction between the sand particles and the microplastic particles, thus enhancing the sand column's ability to retain microplastics.

[0046] Table 1: Surface Zeta potential (mV) before and after iron loading of microplastics and sand particles

[0047]

[0048] Figure 3 The SEM image of the iron-loaded sand grains shows that the surface of the sand grains is rough after iron loading. The more protrusions after iron loading can provide more attachment sites for microplastics, making it possible to completely retain small-diameter microplastics. Figure 4 DLVO energies between 200 nm and 1000 nm microplastic particles were calculated. The lower energy barrier between 200 nm microplastic particles makes them more likely to aggregate on the surface of iron-loaded sand grains, preferentially occupying attachment sites on the sand grain surface; while the higher energy barrier between 1000 nm microplastic particles results in a more dispersed distribution on the sand grain surface. Therefore, 1000 nm microplastics have a higher migration capacity in the sand column. Thus, iron-loaded sand columns can achieve effective separation of 200 nm and 1000 nm microplastics.

[0049] Example 2:

[0050] (1) Preparation of iron-loaded quartz sand

[0051] Mix 40-60 mesh quartz sand thoroughly in a 0.04 mol / L Fe(NO3)3·9H2O solution. Add NaOH solution to adjust the pH to 10. Shake the mixture on a shaker for half an hour. Then, adjust the pH of the mixture to about 6 with HCl (volume fraction 2:3). Shake the mixture on a shaker for 24 hours. Wash the iron-loaded quartz sand with deionized water until it no longer discolors. Dry it in a 60℃ oven.

[0052] (2) Filling of the iron-loaded sand column

[0053] The iron-loaded sand particles were thoroughly wetted with a 0.01 mol / L NaCl background solution and then packed into a glass chromatography column with an inner diameter of 1.0 cm and a height of 10 cm. 300-mesh filters were fixed at both ends of the column to prevent quartz sand loss. Before packing, a certain level of 0.01 mol / L NaCl background solution was pumped into the column using a peristaltic pump. During packing, the liquid level in the column was ensured to always be slightly higher than the quartz sand. After each batch of sand particles was packed, the column was gently tapped with a rubber mallet to avoid introducing air bubbles. The porosity of the iron-loaded sand particles in the column was 45.8%.

[0054] (3) Separation of 100nm and 800nm ​​microplastics (particle size ratio 1:8)

[0055] The sand column was sampled from the bottom, with the top injection tube connected to the recovery tube and sampler. A peristaltic pump controlled the injection. A mixed solution of 100 nm and 800 nm microplastics was prepared using 0.01 mol / L NaCl solution as the background solution, with each microplastic concentration at 10 mg / L. The iron loading of the sand particles was 419.40 mg / kg. After filling the sand column, the 0.01 mol / L NaCl background solution was pumped into the column at a flow rate of 1.5 mL / min for 30 minutes to equilibrate the column system and ensure its stability. Subsequently, a microplastic mixture with a pore volume of 38 was continuously pumped in, and the effluent was collected every 6 minutes using a sampler to determine the concentration of microplastics in the effluent. The concentrations of the two microplastics in the effluent were determined using a dual-wavelength ultraviolet quantification method, and a concentration change graph was plotted.

[0056] Its concentration change is as follows Figure 5 As shown, with the change of injection time, 100nm microplastics are completely retained in the sand column, while 800nm ​​microplastics will penetrate the sand column, thus realizing the separation of 800nm ​​microplastics in the mixed solution.

[0057] Example 3:

[0058] (1) Preparation of iron-loaded quartz sand

[0059] Mix 40-60 mesh quartz sand thoroughly in a 0.04 mol / L Fe(NO3)3·9H2O solution. Add NaOH solution to adjust the pH to 10. Shake the mixture on a shaker for half an hour. Then, adjust the pH of the mixture to about 6 with HCl (volume fraction 2:3). Shake the mixture on a shaker for 24 hours. Wash the iron-loaded quartz sand with deionized water until it no longer discolors. Dry it in a 60℃ oven.

[0060] (2) Filling of the iron-loaded sand column

[0061] The iron-loaded sand particles were thoroughly wetted with a 0.01 mol / L NaCl background solution and then packed into a glass chromatography column with an inner diameter of 1.0 cm and a height of 10 cm. 300-mesh filters were fixed at both ends of the column to prevent quartz sand loss. Before packing, a certain level of 0.01 mol / L NaCl background solution was pumped into the column using a peristaltic pump. During packing, the liquid level in the column was ensured to always be slightly higher than the quartz sand. After each batch of sand particles was packed, the column was gently tapped with a rubber mallet to avoid introducing air bubbles. The porosity of the iron-loaded sand particles in the column was 45.8%.

[0062] (3) Separation of 100nm and 800nm ​​microplastics (particle size ratio 1:8)

[0063] The sand column was sampled from the bottom, with the top injection tube connected to the recovery tube and sampler. A peristaltic pump controlled the injection. A mixed solution of 100 nm and 800 nm microplastics was prepared using 0.01 mol / L NaCl solution as the background solution, with each microplastic concentration of 10 mg / L. The iron loading of the sand particles was 419.40 mg / kg. After filling the sand column, the 0.01 mol / L NaCl background solution was pumped into the column at a flow rate of 2.0 mL / min for 30 minutes to equilibrate the column system and ensure its stability. Then, a microplastic mixture with a pore volume of 38 was continuously pumped in, and the effluent was collected every 4.5 minutes using a sampler to determine the concentration of microplastics in the effluent. The concentrations of the two microplastics in the effluent were determined using a dual-wavelength ultraviolet method, and a concentration change graph was plotted.

[0064] Its concentration change is as follows Figure 6 As shown, with the change of injection time, 100nm microplastics are almost completely retained in the sand column, while 800nm ​​microplastics will penetrate out of the sand column, thus realizing the separation of 800nm ​​microplastics in the mixed solution.

[0065] The above examples demonstrate that when the particle size ratio is less than 1:5, the present invention can effectively separate two microplastics with different particle sizes, and the separation process is simple and feasible, showing good application prospects.

[0066] The above are merely preferred embodiments of the present invention and do not constitute any limitation on the present invention. Any equivalent substitutions or modifications made by those skilled in the art to the technical solutions and content disclosed in the present invention without departing from the scope of the present invention shall be deemed to have remained within the protection scope of the present invention.

Claims

1. A method for effectively separating microplastic particles of different sizes, characterized in that: A mixed solution of two microplastics with different particle sizes is passed into an iron-loaded quartz sand column. The iron-loaded quartz sand is prepared by placing quartz sand in an aqueous Fe(NO3)3 solution and mixing thoroughly, adjusting the pH to alkaline, shaking and mixing, then adjusting the pH to acidic, continuing shaking, and finally washing the iron-loaded quartz sand until it no longer discolors. The iron loading of the iron-loaded quartz sand is 300-700 mg / kg. The smaller-sized microplastics preferentially occupy the adsorption sites on the surface of the iron-loaded quartz sand through competitive adhesion, repelling the larger-sized microplastics from penetrating the sand column, thereby achieving the separation of microplastics of different sizes. The particle size ratio of the smaller-sized microplastics to the larger-sized microplastics is less than 1:

5.

2. The method for effectively separating microplastic particles of different sizes according to claim 1, characterized in that: Adjust the pH of the solution to 10 using NaOH.

3. The method for effectively separating microplastic particles of different sizes according to claim 1, characterized in that: Adjust the pH of the mixture to 6 using HCl.

4. The method for effectively separating microplastic particles of different sizes according to any one of claims 1 to 3, characterized in that: The prepared iron-loaded sand particles were packed into a glass chromatography column for separation of mixed solutions of microplastics with different particle sizes.

5. The method for effectively separating microplastic particles of different sizes according to claim 4, characterized in that: The separation method is as follows: the sample is injected from the lower end of the sand column, and the upper end of the flexible tube is connected to the recovery tube and the sampler. The injection flow rate is controlled at 1.5-2.5 mL / min.

6. The method for effectively separating microplastic particles of different sizes according to claim 4, characterized in that: The mixed solution of microplastics was passed through a 40-60 mesh sand column.

7. The method for effectively separating microplastic particles of different sizes according to claim 4, characterized in that: The concentration of both types of microplastics in the mixed solution was 10 mg / L.

8. The method for effectively separating microplastic particles of different sizes according to claim 1, characterized in that: The iron content of the iron-loaded quartz sand is 419.40-663.06 mg / kg.

9. The method for effectively separating microplastic particles of different sizes according to claim 1, characterized in that: The particle size range of the microplastics is 10-1000 nm; and / or, the background solution for preparing the mixed solution of microplastics is a NaCl solution.

Citation Information

Patent Citations

  • Method for separating micro-plastics and nano-plastics in porous medium by using dissolved organic matters extracted from pig manure and goethite

    CN114619588A